Optimization of a Simplified and Effective Analytical Method of Pesticide Residues in Mealworms (Tenebrio molitor Larvae) Combined with GC–MS/MS and LC–MS/MS - Kim, Leesun (Molecules, 2020)
An effective analytical method was optimized for residues including chlorpyrifos–methyl, deltamethrin, fenoxanil, thiobencarb and fludioxonil in mealworms, the larval form of Tenebrio molitor. They are listed for pest control during wheat cultivation and can be found in wheat-bran feed for growing mealworms in South Korea. Analytes were extracted using acetonitrile and salt packet. Four clean-up methods ((1) MgSO(4) + 25 mg PSA + 25 mg C18; (2) MgSO(4) + 50 mg PSA + 50 mg C18; (3) EMR-lipid(TM) tube; and (4) 10 mL n-hexane) were investigated and the method (1) was selected due to its robustness. Low-temperature precipitation of fat and proteins improved the recoveries. Recoveries from the Method (1) were satisfying with 70–120% with <20% relative SD at a spiking level of 0.01 mg/kg. With the simultaneous sample preparation, fenoxanil, thiobencarb and fludioxonil were analyzed by liquid chromatography tandem mass spectrometry (LC–MS/MS) and chlorpyrifos–methyl and deltamethrin by gas chromatography tandem mass spectrometry (GC–MS/MS). Quantification limits for LC–MS/MS and GC–MS/MS were 0.5 and 2.5 μg/L, respectively. No pesticides of interest were detected in 30 real samples collected across the nation. However, the data can be provided for establishing maximum residue limits for the pesticides in mealworms in response to the positive list system.